First report on the antibody verification of HLA‐ABC epitopes recorded in the website‐based HLA Epitope Registry. Issue 6 (June 2014) - Duquesnoy, R. J.; Marrari, M.; Mulder, A.; da Mata Sousa, L. C. D.; da Silva, A. S.; do Monte, S. J. H.
Abstract The International Registry of Antibody‐Defined HLA Epitopes ( http://www.epregistry.com.br) has been recently established as a tool to understand humoral responses to human leukocyte antigen (HLA) mismatches. These epitopes are defined structurally by three‐dimensional molecular modeling and amino acid sequence differences between HLA antigens. So‐called eplets represent essential components of HLA epitopes and they are defined by polymorphic residues. A major goal is to identify HLA epitopes that have been verified experimentally with informative antibodies. Our analysis has also included data in many publications. As of 1 November 2013, 95 HLA‐ABC antibody‐verified epitopes have been recorded, 62 correspond to eplets and 33 are defined by eplets paired with other residue configurations. The Registry is still a work‐in‐progress and will become a useful resource for HLA professionals interested in histocompatibility testing at the epitope level and investigating antibody responses to HLA mismatches in transplant patients.